Effectiveness of Virtual Laboratory-Based Interactive Learning Media Through a Differentiated Approach to Students' Scientific Literacy - Tirtawaty Abdjul; Abdul Haris Odja; Nurhayati (Postgraduate, University of Mataram, 2024)
This research aims to determine the extent to which the effectiveness of virtual laboratory-based interactive learning media through a differentiated approach can influence students' scientific literacy. The study was conducted on SMP Negeri 1 Tilango, Gorontalo district class VII students. This research uses a one-group pretest-post-test design. Based on the results of the T-Test, it was found that for the experimental class, the average ability of students to identify problems scientifically was 76.67%, the ability to explain scientific phenomena was 79.92%, and to draw conclusions based on scientific evidence was 70.49%. In the Replication class, the average ability of students to identify problems scientifically was 76.46%, the ability to explain scientific phenomena was 81.71%, and the ability to draw conclusions based on scientific evidence was 70.07%. An increase in students' scientific literacy was obtained using the N-Gain test, and the average results obtained in the experimental class were 0.85 (high) and the replication class 0.84 (high). This means that the students' scientific literacy skills in both the experimental and replication classes are in a good category, so it can be concluded that the virtual laboratory-based interactive learning media through a differentiated approach is effectively used as a learning media in science subjects, especially the material on substance and change.